Unmasking the Hidden: A Case of Left Atrial Myxoma with Myriad Presentations Initially Overlooked - Arun B. Shivashankarappa; Pranav S. Kumar; Lakshmana Sridhar; Prasanna Simha Mohan Kumar; Kalpana Saligram Ramegowda; Prabhavathi Bhat (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
Cardiac myxomas are the most common primary cardiac tumors and are usually benign. They vary in size and location, with the left atrium (LA) being the most common site, typically attached to the fossa ovalis. Their manifestations range from asymptomatic to severe obstructive cardiac symptoms, embolic manifestations, or systemic findings, which can often occur without any primary cardiac symptoms. Here is a case of a 48-year-old man who initially presented with ischemic stroke. The myxoma was missed, and he later developed diverse manifestations such as weight loss and anorexia, ultimately presenting with biventricular failure. LA myxoma with biventricular failure is rare. Our patient showed significant improvement in both clinical status and biventricular function following myxoma excision.